The Existence of a Two-class Economy in the Kaldor and Pasinetti Models of Growth and Distribution - Maneschi, A. (Review of Economic Studies, 1974)
Journal Article The Existence of a Two-class Economy in the Kaldor and Pasinetti Models of Growth and Distribution Get access A. Maneschi A. Maneschi Vanderbilt University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 1, January 1974, Pages 149–150, https://doi.org/10.2307/2296405 Published: 01 January 1974